Guillain‐Barré syndrome following COVID‐19 vaccination: An updated systematic review of cases - Nour Shaheen; Abdelraouf Ramadan; Abdulqadir J. Nashwan; Ahmed Shaheen; Shahzaib Ahmad; Karam R. Motawea; Salaheldin Mohamed; Rahma Sameh Mohamed; Sarya Swed; Hani Aiash (Clinical Case Reports, 2023)
Key Clinical Message Guillain‐Barré syndrome (GBS) is a rare but possible complication that may occur after COVID‐19 vaccination. In this systematic review, we found that GBS presented in patients with an average age of 58. The average time for symptoms to appear was 14.4 days. Health care providers should be aware of this potential complication. Abstract Most instances of Guillain‐Barré syndrome (GBS) are caused by immunological stimulation and are discovered after vaccinations for tetanus toxoid, oral polio, and swine influenza. In this systematic study, we investigated at GBS cases that were reported after receiving the COVID‐19 vaccination. Based on PRISMA guidelines, we searched five databases (PubMed, Google Scholar, Ovid, Web of Science, and Scopus databases) for studies on COVID‐19 vaccination and GBS on August 7, 2021. To conduct our analysis, we divided the GBS variants into two groups, acute inflammatory demyelinating polyneuropathy and non‐acute inflammatory demyelinating polyneuropathy (AIDP and non‐AIDP), and compared the two groups with mEGOS and other clinical presentation In this systematic review, 29 cases were included in 14 studies. Ten cases belonged to the AIDP variant, 17 were non‐AIDP (one case had the MFS variant, one AMAN variant, and 15 cases had the BFP variant), and the two remaining cases were not mentioned. Following COVID‐19 vaccination, GBS cases were, on average, 58 years of age. The average time it took for GBS symptoms to appear was 14.4 days. About 56 percent of the cases (56%) were classified as Brighton Level 1 or 2, which defines the highest level of diagnostic certainty for patients with GBS. This systematic review reports 29 cases of GBS following COVID‐19 vaccination, particularly those following the AstraZeneca/Oxford vaccine. Further research is needed to assess all COVID‐19 vaccines' side effects, including GBS.